NOKEN PAPUA: SUMBER PENDIDIKAN KARAKTER BERBASIS KEWIRUSAHAAN INDUSTRI KREATIF - Marit, Elisabeth Lenny (Universitas Papua Manokwari, 2017)
This paper aims to describe Papuan noken in the perspective of the creative industry that has revived the spirit and selfdefense as an individual or community of Papuans. Noken Papua became one of the iconic potential community creative industries and made as part of the cultural heritage that was saved. This paper will discuss Papua›s noken as a source of education of entrepreneurial-based character in creative industry. Joint efforts in building character education through the process of entrepreneurship and knowledge papua as a creative industry. This paper will explore the value of character education contained in the entrepreneurial activities of creative industries papua noken, especially in the effort to form human resources (HR) characterized entrepreneurship.